2017
DOI: 10.5539/ijbm.v12n10p223
|View full text |Cite
|
Sign up to set email alerts
|

Value Relevance of Accounting Information in Explaining Stock Returns in Sri Lanka

Abstract: The value relevance of accounting information is an important area in accounting researches. However the literature provides contradictory conclusions on the value relevance of accounting information in different stock exchanges and there is a very limited knowledge in this regard in Sri Lankan context. Hence this study endeavored to investigate the value relevance of accounting information in explain stock returns considering three traditional accounting performance measures: Earnings Per Share (EPS), Return … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(26 reference statements)
0
0
0
Order By: Relevance
“…The outcome is constant with these findings: Omokhudu OO, Ibadin PO., Uwuigbe and co-workers, Oloidi and Bolade [53,46,51] who located a sizable bad courting between profits per share and proportion price, have been contradicted by means of Mayadunne and Oloidi [44,51] who both observed that income per proportion EPS has a fantastic giant dating with percentage fee. Daye's findings are in keeping with this result even as Samuel, T.E., Pradeep [48] found a considerably terrible correlation among income consistent with percentage and proportion charge.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcome is constant with these findings: Omokhudu OO, Ibadin PO., Uwuigbe and co-workers, Oloidi and Bolade [53,46,51] who located a sizable bad courting between profits per share and proportion price, have been contradicted by means of Mayadunne and Oloidi [44,51] who both observed that income per proportion EPS has a fantastic giant dating with percentage fee. Daye's findings are in keeping with this result even as Samuel, T.E., Pradeep [48] found a considerably terrible correlation among income consistent with percentage and proportion charge.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…Even though consolidated financial records changed into greater fee relevant than separated financial facts, they observed that common, accounting information on each consolidated and separated financial data had been relevant to price. Mayadunne [44] studied how accounting information affects traders' choices about an organization's cost. The dreams of the observer had been to decide the connection between the market charge and the price relevance of accounting statistics, as well as the impact that accounting facts have on the decisions made with the aid of buyers.…”
Section: Empirical Reviewmentioning
confidence: 99%